Analysis of Information Support of Knowledge Management in Ukraine - Oliinyk, O. O. (Statistics of Ukraine, 2019)
The article defines the place and components of IT solutions in the knowledge management system. The author substantiates that the use of modern IT solutions in the knowledge management system is an essential component of creation, search, transfer, exchange, development and effective use of knowledge. A large number of different technologies are used to integrate into a single complex of knowledge management system, including traditional automation systems and information retrieval systems, e-mail, corporate networks and Internet services, databases and data warehouses, electronic document management systems, specialized data processing programs, expert systems and databases knowledge In this case, a computer remains as a main tool of information management knowledge management in Ukraine. The scholar analysed the dynamics of the major indicators of computer devices’ use of by enterprises. The paper determined that not all enterprises in Ukraine use computers in their business activities. The proportion of enterprises, which used computers in 2017, amounted for 95.4%, which is by 0.2% more in comparison with 2015. The best situation in this aspect is in such types of economic activities as professional, scientific and technical activities; information and telecommunications; water supply; sewage, waste management. However, on average only every third employee in Ukraine used a computer to perform his/her professional duties. The author examined the main Internet-based jobs, where traditional activities are the most popular ones, namely: sending or receiving various e-mails, receiving information about goods and services. At the same time, videoconferencing is less popular, which is a negative factor in creating effective communication in the transmission, dissemination and exchange of knowledge. The paper explored the degree of using the possibilities of a corporate website for personnel training. The author determined that only every tenth enterprise in Ukraine uses its own website for the professional development of the employees. The scholar substantiated the features of social media, which promote the efficiency of their use as a tool for knowledge management. Exchanging views, opinions or knowledge within the enterprise and engaging customers in the development or innovation of goods and services remain the least popular objectives of social media work.